Design, construction, modeling and estimation of the second stage linear model of laboratory drone with cold gas thrusters based on genetic algorithm - Seyyed Ali Saadatdar Arani; Mehran Nosrstollahi; Alireza Ahangarani Farahani; Meysam Delalat (مجله مدل سازی در مهندسی)
In this paper, the process of designing and construction of three-drive laboratory Drone system with cold gas thrusters as well as modeling and estimation of its model parameters are presented. These three thrusters are designed with an angle difference of 120 degrees to control the pitch and roll angles. According to the structure of the designed platform, a three-inputs-two-outputs linear model is considered for modeling the mentioned system, and all connections between inputs and outputs are second-order linear models. The parameters of the model have been extracted based on the collection of laboratory data and the use of genetic algorithm. The results obtained from the simulation based on the extracted model and the comparison with the results of the practical tests indicate that a suitable modeling and estimation of the system has been provided. The results show that there is 16% error for modeling and estimation around the roll axis and 19% around the vertical axis, so the estimation around the roll axis is better.